Оценка влияния гемостатических материалов на концентрацию кальция крови (Исследования и практика в медицине)
The aim of the study is to estimate influence of haemostatic materials on concentration of calcium of blood in in vitro experiment.Methods. As materials of a research used the following samples of haemostatic materials: control group (group No. 1), Tachocomb (No. 2), Gelita-Spon Standard (No. 3), Surgicel Fibrillar (No. 4), the samples of styptic sponges developed together with Linteks (St. Petersburg, Russia) on a basis sodium- carboxymethylcellulose (Na-CMC) with various modifications: Na-CMC+ tranexamic acid, pressed (No. 5), Na-CMC+ tranexamic acid, not pressed (No. 6), Na-CMC pressed (No. 7), Na-CMC not pressed (No. 8). Results. Proceeding from the obtained data, we will note that the smallest concentration of calcium is defined at immersion in blood of samples of group No. 4 (Surgicel Fibrillar) – 1.64 mmol/litre, and the greatest – 2.39 mmol/litre at a research of samples of group No. 7 (Na- CMC pressed). Conclusion. It is established that haemostatic materials on the basis of collagen and derivatives of cellulose considerably influence formation of a clot in in vitro experiment, in comparison with styptic means on the basis of medical gelatin. It is shown by decrease in level of calcium in blood serum after introduction of the tested samples.